2015
DOI: 10.1155/2015/109593
|View full text |Cite
|
Sign up to set email alerts
|

An Association between Single Nucleotide Polymorphisms of Lys751GlnERCC2Gene and Ovarian Cancer in Polish Women

Abstract: Aim. The aim of this study was to evaluate the role of the Lys751Gln (rs13181) ERCC2 gene polymorphism in clinical parameters and the risk for development of ovarian cancer. Material and Methods. The study consisted of 430 patients with ovarian cancer (mean age: 53.2 ± 10.11) and 430 healthy subjects (mean age: 50.31 ± 18.21). Analysis of the gene polymorphisms was performed using the PCR-based restriction fragment length polymorphism (PCR-RFLP). The odds ratios (ORs) and 95% confidence intervals (CIs) for eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
(32 reference statements)
0
9
0
Order By: Relevance
“…Mutations associated with ↑ risk [73] N/A Response to PARPi (in vivo and in vitro evidence) [ [237] SNPs associated with prognosis [238] SNP associated with severe neutropenia in patients treated by cisplatin-based chemotherapy [239] ERCC1 N/A SNPs associated with ↑ OS [240] SNP associated with ↑ risk of nephrotoxicity in patients treated by cisplatin-based chemotherapy [239] Direct repair MGMT N/A N/A Likely to drive chemoresistance [170] ALKB N/A N/A ALKBH5 downregulation contributes to PARPi resistance in BRCA-deficient EOC [241] Author Contributions: Writing-original draft preparation, K.T., A.C., J.H., K.K. ; writing-review and editing, R.V., L.V., P.V.…”
Section: Brca1mentioning
confidence: 99%
“…Mutations associated with ↑ risk [73] N/A Response to PARPi (in vivo and in vitro evidence) [ [237] SNPs associated with prognosis [238] SNP associated with severe neutropenia in patients treated by cisplatin-based chemotherapy [239] ERCC1 N/A SNPs associated with ↑ OS [240] SNP associated with ↑ risk of nephrotoxicity in patients treated by cisplatin-based chemotherapy [239] Direct repair MGMT N/A N/A Likely to drive chemoresistance [170] ALKB N/A N/A ALKBH5 downregulation contributes to PARPi resistance in BRCA-deficient EOC [241] Author Contributions: Writing-original draft preparation, K.T., A.C., J.H., K.K. ; writing-review and editing, R.V., L.V., P.V.…”
Section: Brca1mentioning
confidence: 99%
“…A number of molecular epidemiological studies have shown that polymorphisms of ERCC1 and ERCC2 genes can affect susceptibility towards colorectal cancer [6], lung cancer, larynx cancer [10], ovarian cancer [14], glioma [12]. Sileng A. and et al (2016) observed an risk-increase in pancreatic cancer for those who carry minor alleles of the polymorphic variant of ERCC2 rs13181 gene [5].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that this Lys751Gln polymorphism could decrease DNA repair capacity [ 46 ]. In a study conducted in Poland with 430 patients and 430 controls, Magdalena et al [ 47 ] found that the Gln/Gln genotype of rs13181 is associated with an increased risk of ovarian cancer. In our earlier study investigation of the association between two XPD polymorphisms (rs238406 and rs13181) and esophageal squamous cell carcinomas risk, we found that rs238406, but not rs13181, was associated with elevated disease risk [ 34 ].…”
Section: Discussionmentioning
confidence: 99%